Legislators, Judges, and Professors - Fleischer, Holger; Basedow, Jürgen; Reinhard Zimmermann (Mohr Siebeck, 2016)
As lawyers we are normally interested in various substantive areas of law; and as comparative lawyers we are interested in finding out about the differences and similarities between national legal systems. But from time to time we should also reflect on how we think and operate, and look at basic questions of legal methodology - both for the sake of understanding better what we do as lawyers immersed in our own legal systems and as lawyers attempting to assess and comprehend how foreign legal systems work. The nine essays in this volume are devoted to the topics of law-making today (with a focus on Japan, Turkey and Russia), judicial decision-making today (with a focus on England and Wales, Switzerland and Argentina), and legal scholarship today (with a focus on the United States, France and South Africa); and they thus revolve around the three protagonists of legal development: legislators, judges and professors.